Constitution Making and Nation-State Imagination: A Historical Comparison, 1945-2002 - Herlambang Perdana Wiratraman (Mimbar Hukum, 2026)
Abstract In Indonesia’s history, the making of the constitutional foundation has been shaped by its political context. From the decolonization process till present, the making of the constitution has been intervened by various actors, both national and international parties. Hence, constitution changes are socially and politically complex. The complexities are represented in constitution-making governance, process, and its debates in the substantive drafting. This article focuses on how the constitution-making processes and its debates regarding issues of human rights and fundamental freedom have been contested since the very beginning of Indonesia’s independence, and how this debate provides answers to the cases, processes, substance, and implementation involved in Indonesia’s constitution making. It is clear in a comparative analysis, using Arato’s model, that the constitution-making during the amendment period (1999-2002) is the best process that involved civil society and substantially more progressive. However, this argues that understanding the constitution-making would play important role in underpinning Indonesia’s nation state imagination. Abstrak Dalam sejarah Indonesia, pembentukan landasan konstitusional telah dibentuk oleh konteks politiknya. Dari proses dekolonisasi hingga saat ini, terlihat bahwa pembentukan konstitusi telah diintervensi oleh berbagai aktor, baik nasional maupun internasional. Oleh karena itu, perubahan konstitusional bersifat kompleks secara sosial dan politik. Kompleksitas tersebut terdapat dalam model pembentukan konstitusi, proses, dan perdebatan dalam penyusunan substansinya. Pembahasan artikel ini berfokus pada bagaimana proses pembentukan konstitusi dan perdebatannya mengenai beberapa isu hak asasi manusia dan kebebasan dasar sebagai gagasan yang diperdebatkan sejak awal kemerdekaan Indonesia, dengan memberikan jawaban atas penyebab, proses, substansi, dan implementasi yang terlibat dalam pembuatan konstitusi baru di Indonesia. Jelas dalam analisis komparatif, berbasis model Arato, bahwa pembentukan konstitusi selama periode amandemen (1999-2002) merupakan proses terbaik dalam melibatkan masyarakat sipil dan secara substansial lebih progresif. Namun, hal ini menunjukkan bahwa memahami pembuatan konstitusi akan memainkan peran penting untuk mendukung imajinasi negara bangsa Indonesia.